An assessment of quality of care service provided to people living with HIV/AIDS by a secondary healthcare centre at Osogbo, Nigeria - S.A. Olowookere; J.O. Olaitan; N.A. Adeleke; P.B. Olaitan; E.G. Adepoju (South African Family Practice)
Objective: The objective of this study was to assess the quality of service provided to people living with human immunodeficiency virus (HIV)/acquired immune deficiency syndrome (AIDS) at a secondary healthcare centre at Osogbo, Nigeria.